Numerical Analysis of Compatible Finite Elements of Different Order in Two-Dimensional Problems of Elasticity - Braga, F.; Rega, G.; Vestroni, F. (Engineering Transactions, 1978)
A large number of compatible finite element models for plane elasticity problems has been presented in the last decade. On the contrary, the number of studies so far carried out regarding the elements is small. This paper is mainly concerned with the evaluation of the efficiency of different comparison of the behaviour of compatible triangular elements of different order. Such a comparison regards mainly the results associated with LST and QST elements for different values of the number of degrees of freedom in the analysis of problems for which analytical solutions are available. Attention is focused separately on displacement and stress fields by analysing the convergence of the elements as well as the global and local approximation. A numerical analysis is also performed in order to compare the efficiency of two methods suited for encompassing lack of uniqueness of stress nodal values, as usually encountered in the compatible formulation, i.e. the simple average and the method based on the theory of conjugate approximations.